Free Radical Scavenging Potential of Nelumbo Nucifera Gaertn Flowers (White and Pink) - Durairaj, Brindha; Dorai, Arthi (International Journal of Natural Sciences Research, 2014)
Considering the growing interest in assessing the antioxidant capacity of herbal medicine, the present research was aimed to explore antioxidant potentials of NelumbonuciferaGaertn (Nelumbonaceae )flower in-vitro. Hydroethanolic extract of white Nelumbo nucifera (HEWNN) flower and pink Nelumbonucifera (HEPNN) flower were investigated for Total antioxidant capacity. Antioxidant activity by ferric thiocyanate (FTC), Thiobarbituric acid, Ferric reducing antioxidant power, Phosphomolybdenum, Hemoglobin glycosylation, and reducing power methods were estimated in both flowers and compared with standard ascorbic acid in dose dependent manner. In-vitro assays to inhibit free radicals such as 1,1-diphenyl 2-picryl radical (DPPH), superoxide, nitric oxide, hydroxyl radical and hydrogen peroxide (H2O2) were also carried out. Antioxidant capacity measured by FTC and compared with TBA method showed low absorbance values than control which indicated a high level of antioxidant potential. Both HEWNN and HEPNN flower extracts exhibited maximum activity 16.53 mg and 14.21 mg at 1000 µg/ml extract concentration in FRAP method and 62.5 mg and 56.3 mg ascorbic acid equivalents at 500 µg/ml extract concentration in phosphomolybdenum method. There was also significantly high antioxidant activity (55.5% & 41.6%) of haemoglobin followed reducing power (0.351 & 0.248 Abs) at same 500 µg/ml extract concentration. The results obtained suggest that alkaloids, phenols and flavonoids in flowers yield considerable antioxidant activity. The maximum scavenging activity of HEWNN and HEPNN against DPPH (67.52% & 55.51%), superoxide radical (81.2% & 64.5%), nitric oxide (70.2% & 57.7%), and hydroxyl radical (60.53% & 46.72%) and H2O2 (54.29% & 48.13%) were evaluated. The IC50 values were compared to the standard ascorbate in a dose dependent manner. The results obtained suggest that on comparison with HEPNN flower, HEWNN flower extract may act as a better chemo preventive agent providing promising antioxidant property and offering effective protection from free radicals. Our results clearly indicate that both HEWNN and HEPNN flower extracts have potent antioxidant and free radical scavenging capacity in all assays. Nelumbonucifera can be used as a lead compound for drug development in future.